2012
DOI: 10.1021/ct300152t
|View full text |Cite
|
Sign up to set email alerts
|

Short Time Dynamics of Ionic Liquids in AIMD-Based Power Spectra

Abstract: Power spectra of several imidazolium-based ionic liquids, 1,3-dimethylimidazolium chloride, 1-ethyl-3-methylimidazolium thiocyanate, 1-ethyl-3-methylimidazolium dicyanamide 5, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium thiocyanate, and 1-butyl-3-methylimidazolium dicyanamide, are presented based on ab initio molecular dynamics simulations. They provide an alternative tool of analysis of several electronic structure-based properties, in particular, those related to the strength of hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 89 publications
2
83
0
3
Order By: Relevance
“…Nonetheless, the lower wavenumber contributions of the C 2 ―H stretching profile are dominated by the strongly H‐bonded configurations. This is also confirmed by the progressive redshift of the ring C―H contributions with increasing anion basicity . The latter observation is admitted by both groups who initiated the debate …”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Nonetheless, the lower wavenumber contributions of the C 2 ―H stretching profile are dominated by the strongly H‐bonded configurations. This is also confirmed by the progressive redshift of the ring C―H contributions with increasing anion basicity . The latter observation is admitted by both groups who initiated the debate …”
Section: Resultsmentioning
confidence: 57%
“…Nevertheless, the latest studies on this issue which use IR spectroscopy of EmimTFSI as single ion pairs in helium nanodroplets or in jet‐cooled IL vapor suggest that both effects contribute to the complex broad low‐wavenumber part of the ring C―H stretching profile which is attributed to the C 2 ―H stretching mode. Ab initio molecular dynamics using a dispersion‐corrected density functional showed that despite the fact that the spectral contributions stemming from the C 2 ―H fragment are revealed at somewhat lower wavenumbers they cover rather broad range strongly overlapping with the C (4,5) ―H contributions. Nonetheless, the lower wavenumber contributions of the C 2 ―H stretching profile are dominated by the strongly H‐bonded configurations.…”
Section: Resultsmentioning
confidence: 99%
“…The power spectrum P ( ω ) is obtained by first performing a molecular dynamics run and then calculating the Fourier transform of the total velocity autocorrelation A v ( τ ): 97 Avfalse(τfalse)=n=1Natomsnormaldtvnfalse(tfalse)·vnfalse(t+τfalse) Pfalse(ωfalse)=true|mnormaldτAvfalse(τfalse)enormaliωτtrue|…”
Section: Methodsmentioning
confidence: 99%
“…The most important one is that classical modelling is not suitable for the determination of the potential of zero charge (PZC), which is defined as the value of ∆Ψ for which σ + = σ − = 0 ; of course a value can be extracted from C-V curves but those cannot be compared to experiments because it corresponds to the position of the Fermi level of the electrode, an electronic property which can only be caught at the ab initio level. Ab initio molecular dynamics may provide a solution to this problem in future years 101 , but this technique remains substantially too expensive in computational resources because of the large cells and long relaxation times necessary for the IL interfacial studies -for the moment it is limited to the study of relatively small bulk ionic liquids samples [102][103][104] . The surface charges and the relative potentials fluctuate on long timescales so that their averages are associated with substantial error bars; for example on figure 5.…”
Section: B Capacitancementioning
confidence: 99%